Correction of Anemia in Chronic Kidney Disease With Angelica sinensis Polysaccharide via Restoring EPO Production and Improving Iron Availability - Wang, Kaiping; Wu, Jun; Xu, Jingya; Gu, Saisai; Li, Qiang; Cao, Peng; Li, Mingming; Zhang, Yu; Zeng, Fang (Frontiers in Pharmacology, 2018)
Given the limited efficacy and potential disadvantages of erythropoiesis-stimulating agents (ESAs) in treating anemia of chronic kidney disease (CKD), the development of better alternative therapies has become a priority. The primary purpose of this study is to investigate the effects of Angelica sinensis polysaccharide (ASP) and its underlying mechanism in the treatment of renal anemia. In the present study, we found that ASP could enhance hypoxic induction of EPO in Hep3B cells, with a mechanism that involved the stabilization of HIF-2α protein. In parallel, ASP rescued the inhibition of EPO, induced by proinflammatory factor TNF-α, through blocking GATA2 and NF-κB activation. In a rat model of adenine-induced anemia of CKD, oral administration of ASP corrected anemia and alleviated renal damage and inflammation. By increasing the accumulation of HIF-2α protein and reducing the expression of NF-κB and GATA2 as well as pro-inflammatory cytokines, ASP stimulated both renal and hepatic EPO production, and resulted in an elevation of serum EPO. The restoration of EPO production and EPOR mRNA expression with ASP treatment activated EPOR downstream JAK2/STAT5 and PI3K/Akt signaling, induced their target genes, such as Bcl-xL, Fam132b and Tfrc, and increased Bcl-2/Bax ratio in bone marrow-derived mononuclear cells of CKD rats. Furthermore, we found that ASP suppressed hepatic hepcidin expression, mobilized iron from spleen and liver and increased serum iron. These findings demonstrate that ASP elicits anti-anemic action by restoring EPO production and improving iron availability in the setting of CKD in rats.